A review of global strategies promoting the conversion of food waste to bioenergy via anaerobic digestion. (November 2017) - De Clercq, Djavan; Wen, Zongguo; Gottfried, Oliver; Schmidt, Franziska; Fei, Fan
Abstract: The objective of this paper is to review policies around the world that promote the conversion of food waste to biogas. We review policies and operational projects from a diverse set of case study countries including South Korea, China, France, Germany, and the United Kingdom. Using a four-step analysis methodology that focuses on each country's (1) food waste background, (2) food-waste-to-biogas policy environment, (3) status quo of food waste-to-biogas projects and (4) future policy/project-level challenges, we provide a comprehensive cross-country review of food waste-to-biogas policy developments. We find that, while each surveyed country has unique strengths and weaknesses in their policy structure, Asian and European countries also do face similar bottlenecks in the food waste-to-biogas sector. Some specific findings include: (1) highly centralized policies in Asian case countries such as China and South Korea have led to the rapid build-up of a food waste-to-biogas sector; (2) European case countries such as France and the United Kingdom have succeeded in implementing policies that incentivize the production of multiple outputs within treatment facilities; (3) South Korea is a good example of how countries can implement smart waste management systems to decrease the volume of FW generated at the source; (4) South Korea, Germany and France have successfully built many co-digestion projects treating FW together with other waste sources, indicating that project operators in countries have understood the multiple benefits of co-digestion. The geographic breadth of the case studies, and the best practices and challenges identified for each country, should prove highly useful for policy-makers in developing countries who are seeking to enhance food waste management via anaerobic treatment methods.